(untitled) (Research, Society and Development, 2021)
Human milk is considered the main source of nutrients and energy for babies from a nutritional, immunological, and food security point of view. The best way to ensure the supply of the necessary nutrients for the infant is through breast milk, however, when the practice of breastfeeding is impossible, the use of Infant Formula appears as an alternative for the baby’s feeding. The Interesterification process of mixtures between solid fats and vegetable oils can form products with excellent characteristics called structured lipids, which can be used as substitutes for human milk fat in infant formulas. The interesterification enzymatic offers the advantage of greater control over the positional distribution of fatty acids in the final product, due to the selectivity and regiospecificity of lipases in fatty acids. This work brought together recent work on the fat substitute for the production of human milk by interesterification enzyme. Through the search for references, it can be noted that several groups of researchers in the world work with tests to improve and adjust the interesterification technique and the use of the best enzyme for the production of substitutes from different natural sources of oils and fats. However, there are still not many registrations of patented products. In this way, more research must be developed to arrive at a substitute product with the best characteristics for it to be submitted for a patent.